STUDYING THE STATE OF HORSE DISTAL LIMB SEGMENT IN THE HORSE CLUB “ASTRIDE RIDING IN POLTAVA” - Kulynych, S.M.; Omelchenko, G. O.; Avramenko, N. O.; Zezekalo, M.A.; Karpenko, I.O. (Scientific Progress & Innovations, 2020)
The article presents the results of studying the condition of horse distal limb segment in the horse club “Astride Riding in Poltava”, spreading surgical pathology, etiological factors, and symptoms. The aim of the work was to conduct research in the equestrian club among the available horses in order to determine the condition of the distal limb segment. There were the following tasks of the study: to assess the condition, spreading, causes, planimetric examination of the distal limb segment in horses. It has been proven that among the horses, the most common lesions are the periople loss (13 animals or 86.6 %), the appearance of slant (26.6 %), flat (20.0 %) and straight hooves (20.0 %), and also wounds and fractures (13.3 %). The absence of periople in the area of the hoof head and the presence of superficial destruction of the horn is due to drying of the hoof horn, deterioration of the diet, deformation, cracks, improper organization of orthopedic work and imperfect construction of exercising areas. The symptoms of periople destruction were malacia in the range from 1/5 to 2/5 of the epidermis surface layers in the area of the hoof head, at flat hooves, thinning of the hoof sole was observed, at slant hooves – the formation of steep wall on one side of the hoof and sloping wall on the other one, at long hooves – the reduction of toe angle, at straight hooves – the increase in toe angle, sheeting of horn tubules by cracks and the formation of purulent defect in wounds. The ratio of the height of the anterior dorsal wall to the heel is a very informative prognostic indicator of the possible further occurrence of orthopedic pathology (an increase to 1.2 indicates the appearance of straight hooves in the pony and an increase to 2.2 – the excessive rubbing sore the heel). The deformities detected by us affected the animals in different ways: at slant and straight hooves no changes in the general condition of the animals were observed, at long hooves there were toe joint flexor enlargements as a result of constant heel support, at flat hooves lameness occurred with excessive rubbing the horny layer against asphalt. The size of the dorsal wall and heel depends on the animal age and breed, as well as timely conducted orthopedic work.